2020
DOI: 10.12962/j24433527.v0i1.6789
|View full text |Cite
|
Sign up to set email alerts
|

Building Customer Citizenship Behavior from Relationship Quality and Perceived Value Perspective in Online Transportation Service

Abstract: Recently, Customer Citizenship behavior (CCB) has become a research focus in marketing. However, not many researches focus on the antecedent of this variable from the marketing behavior perspective. The research objective is to examine the effect of Relationship Quality and Perceived Value on CCB in online transportation services and Customer Satisfaction as the mediation in this relationship. The research involved 400 online transportation customers in Indonesia who used a minimum of three times in this trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(35 reference statements)
1
0
1
Order By: Relevance
“…Furthermore, the results of the study are partially consistent with van Tonder and Heymans study's findings [74] who indicated that perceived value dimensions (perceived ease of use and perceived usefulness) indirectly affect (through a trust) customer citizenship helping behavior. On the other hand, the findings of the study are inconsistent with the results of Suryani and Listyarti [98], who concluded that CPV insignificantly affects CCB. Upon the previous findings, it could be concluded that the higher the GPV, the greater the perceived CCB and vice versa.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results of the study are partially consistent with van Tonder and Heymans study's findings [74] who indicated that perceived value dimensions (perceived ease of use and perceived usefulness) indirectly affect (through a trust) customer citizenship helping behavior. On the other hand, the findings of the study are inconsistent with the results of Suryani and Listyarti [98], who concluded that CPV insignificantly affects CCB. Upon the previous findings, it could be concluded that the higher the GPV, the greater the perceived CCB and vice versa.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of SEM supports the results of previous studies that have been conducted in various contexts such as the airline industry [76], the tourism industry [97], online-only retailers [74], and the service context [58]. This finding is in line with the results of Woo [76] and Tsaur et al [98], who concluded that CPV positively affects CCB. In their empirical study, Cheng et al [58] demonstrated that CPV plays a vital role in enhancing CCB.…”
Section: Discussionsupporting
confidence: 90%